2016
DOI: 10.3329/bjms.v15i3.30193
|View full text |Cite
|
Sign up to set email alerts
|

12-Weeks programmed aerobics dance reduced body mass index and waist circumference of young women

Abstract: Abstract:Background: Body composition is one of the parameters to evaluate the level of physical fitness. Body composition can be assessed by simple tools like body mass index and waist circumference. This tools also usefull to predict risks for cardiovascular diseases such as metabolic syndrome and dyslipidemia in which the prevalence continues to increase worldwide. Programmed aerobic dance is one of the physical exercises that is quite popular these days that is expected can reduce body mass index and waist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It has been widely promoted with its unique rhythm, spectacle, and fitness. However, the study of the theoretical significance of aerobics is in a state of stagnation, especially the development and application of aerobics in middle schools, and the culture derived from aerobics is limited by teachers and school culture, and psychological research [ 5 ]. In the mid-1980s, the aerobics movement gradually started in the middle school physical education and health curriculum.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…It has been widely promoted with its unique rhythm, spectacle, and fitness. However, the study of the theoretical significance of aerobics is in a state of stagnation, especially the development and application of aerobics in middle schools, and the culture derived from aerobics is limited by teachers and school culture, and psychological research [ 5 ]. In the mid-1980s, the aerobics movement gradually started in the middle school physical education and health curriculum.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The aim of workout is to improve body composition and joint mobility, increase muscle mass, provide endurance and gain flexibility. A combo exercise performed with the movements that support the big muscles groups, consisting of various dance choreographies, without a break for 50 minutes, keeping the heart rate around 60-70% accompanied by popular music (Sulistyoningrum and Candrawati, 2016;Benjamin and Daves, 2015).…”
Section: Soul Beat (Dance-based Aerobic Training)mentioning
confidence: 99%
“…This type of training is designed to improve heartbeats, respiratory system, muscle tonus and mass, body mass index, etc., and all of these are supposed to happen without threatening the weak points of people caused by age or avoiding stimulations of the recovered injures and being more enjoyable for practitioners. Even if the is not direcly to this training the current literature indirectly proved the positive effects on the body composition features such as fat percentage, muscle mass, body mass index etc (Sulistyoningrum and Candrawati, 2016;Oktay, 2018;Serin, 2020). Nevertheless, the effects of this kind of training on balance ability are not proven in current literature, and the absence of the research can be seen.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, obesity and lack of exercise are both associated with asthma symptoms and treatment responses [9]. Sulistyoningrum's research found that regular aerobic aerobics can reduce body weight and waist circumference well [10]. Wen studied the effect of short-term aerobic exercise on bone metabolism and functional health of postmenopausal women [11].…”
Section: Introductionmentioning
confidence: 99%